Neotropical freshwater fishes imperilled by unsustainable policies - Pelicice, Fernando M.; Azevedo-Santos, Valter M. [UNESP]; Vitule, Jean R. S.; Orsi, Mario L.; Lima, Dilermando P.; Magalhaes, Andre L. B.; Pompeu, Paulo S.; Petrere, Miguel; Agostinho, Angelo A. (Wiley-Blackwell, 2017)
Neotropical freshwater fishes are the most diverse on the planet (>5,500 species), although nations in Latin America have been negligent regarding their conservation. National policies have historically encouraged unsustainable practices, and recent decades have witnessed a sharp increase in harmful activities. Our aim with this review was to expose this situation and illustrate how national policies constitute the main threat to freshwater fish biodiversity. We explain that the most devastating, pervasive and systemic threats are rooted in official policies, particularly unsustainable activities (e.g. hydropower, water diversion, mining, aquaculture, agriculture and fishing), poor management/conservation (e.g. fish stocking and passages) and harmful legislation (e.g. poor licensing, non-native species). We provide a broad portrait of the Neotropical scenario, where unsustainable policies have caused considerable damage to freshwater ecosystems, and focus on major examples from Brazil, where development projects have caused large-scale losses to fish biodiversity. Such modus operandi of human development is incompatible with the persistence of biodiversity, and no simple solution is available to correct or minimize its effects. The current situation demands a profound behavioural shift towards better practices and policies, or these multiple high-impact activities will continue eroding freshwater fish biodiversity and impairing essential ecosystem services.
Keywords: biodiversity loss; conservation; economy; ecosystem function; legislation; policy